2011
DOI: 10.1074/jbc.m111.232801
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ATP-sensitive Potassium (KATP) Channels in the Loss of Beta-cell Function Induced by Human Islet Amyloid Polypeptide

Abstract: Islet amyloid polypeptide (IAPP) is a major component of amyloid deposition in pancreatic islets of patients with type 2 diabetes. It is known that IAPP can inhibit glucose-stimulated insulin secretion; however, the mechanisms of action have not yet been established. In the present work, using a rat pancreatic beta-cell line, INS1E, we have created an in vitro model that stably expressed human IAPP gene (hIAPP cells). These cells showed intracellular oligomers and a strong alteration of glucose-stimulated insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 60 publications
4
46
0
1
Order By: Relevance
“…We have previously seen that hIAPP-INS1E cells showed no change in cell death and no change in ER stress marker CHOP when compared to rIAPP-INS1E control cells [26]. Here, we found that the upstream pathways involved in ER stress, such as sXBP1 or ATF3, were not affected, confirming that hIAPP overexpression does not lead to ER stress under basal conditions (11 mM glucose).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We have previously seen that hIAPP-INS1E cells showed no change in cell death and no change in ER stress marker CHOP when compared to rIAPP-INS1E control cells [26]. Here, we found that the upstream pathways involved in ER stress, such as sXBP1 or ATF3, were not affected, confirming that hIAPP overexpression does not lead to ER stress under basal conditions (11 mM glucose).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, we have detected toxic intracellular aggregates in a rat pancreatic beta-cell line overexpressing hIAPP, which lead to a defective insulin and IAPP secretion in response to glucose [26]. Nevertheless, the role of hIAPP overexpression and ER stress induction has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Casas et al demonstrated that extracellular hIAPP aggregation is associated with ER stress responses in mouse β-cells, by an intracellular signaling that involves downstream inhibition of the ubiquitin–proteasome pathway, contributing to β-cell apoptosis 77,78. Nevertheless, in a rat pancreatic β-cell line overexpressing hIAPP, the detection of toxic intracellular oligomers, which lead to defective insulin and IAPP secretion levels in response to glucose, did not change the expression of genes involved in ER stress 79. These results agree with other findings with hIAPP transgenic mice, in which the authors demonstrated that amyloid formation was not associated with significant increases in the expression of ER stress markers 80.…”
Section: Stress Inflammation and The Activation Of Apoptotic Signalingmentioning
confidence: 99%
“…However, the same final results would be achieved indirectly if hIAPP inhibits of the ATP-sensitive potassium channel (K ATP ) closure which would prevent the ␤-cell membrane depolarization required to induce Ca 2+ channel opening. This interesting problem was addressed by Soty et al [94] who, working with an hIAPP transgenic rat pancreatic ␤-cell line, found that membrane depolarization with 30 mM KCl, raises the intracellular Ca 2+ concentration and induces a very strong secretion of insulin, discarding the proposal that the reduction of GSIS in hIAPP-treated islets could be the result of hIAPP inhibition of voltage-gated Ca 2+ channels [93]. However it should be kept in mind that GSIS may be affected differently by hIAPP if it is added externally to islets or if it is overexpressed endogeneously in transgenic cells.…”
Section: Effect Of Hiapp On Plasma Membrane Channelsmentioning
confidence: 96%
“…As is well known ATP-sensitive potassium (K ATP ) channels are constituted by four pore-forming (Kir6.2) subunits and four regulatory sulfonylurea receptors (SUR1) [95]. There is a marked alteration in glucose-stimulated insulin and hIAPP secretion in the transgenic cells expressing hIAPP [94]. The cells, which show intracellular oligomers but no evidence of enhanced apoptosis or ER stress, are not responsive to induction of insulin and hIAPP secretion by glucose or tolbutamide.…”
Section: Effect Of Hiapp On Plasma Membrane Channelsmentioning
confidence: 97%